Critical thinking and problem-solving skills of visually impaired female national judo team athletes - Demiral, S. (Journal of Education and Training Studies, 2019)
A high level of critical thinking and problem-solving skills in visually impaired female national judo team athletes is an important factor in increasing their performance and for their high performance. The aim of this study was to examine critical thinking and problem-solving skills of visually impaired female national judo team athletes. The sample of the study was composed of visually impaired female athletes (n=15) in 2015 national team. A Personal Information Form, the California Critical Thinking Disposition Inventory and the Problem Solving Inventory were used as data collection tools. The data obtained in this study were analyzed using SPSS 17 software. Evaluation of the data analysis revealed that there was no statistically significant difference among groups in total Problem Solving Inventory and Critical Thinking Disposition Inventory scores in terms of age group or age of starting judo (p>0.05). There was no statistically significant relationship between total problem-solving and total critical thinking disposition scores of athletes (p>0.05). As a result, judo coaches are thought to play an important role in the development of strategies for increasing athletes` problem-solving and critical thinking skills and in the development of their sporting performance, particularly in the development of high performance.